Ten years experience with the first approved biosimilar recombinant human growth hormone drug in normal clinical practice - Juan Pedro López-Siguero; Margarida Palla García; Elena Martínez Busto; Francisco José Rebollo; Manuel Pombo (Elsevier, 2018)
Introduction: Recombinant human growth hormone (rhGH) is the first biosimilar drug approved by the European Medicines Agency in 2006, using the biosimilar registration process. It was authorised for the treatment of growth hormone deficiency, and growth disorders associated with Turner's syndrome, chronic renal failure, Prader-Willi syndrome, and growth disorders in children/adolescents born small for gestational age, and replacement therapy in adults with pronounced growth hormone deficiency. Materials and methods: This review is focused on the scientific evidence published about this drug in the last ten years, including the clinical trials on which the approval of the regulatory authority is based, and the most relevant studies evaluating the clinical impact of the drug in clinical practice. Results: The equivalence between biosimilar and original product has been confirmed in the clinical trials published by Romer et al. and López-Siguero et al. Furthermore, studies carried out in real-life conditions confirm its long-term efficacy and safety, as well as the absence of clinical impact by switching treatment from the original to the biosimilar product. Conclusion: The number of patients receiving this medication has continuously increased since its approval. Its equivalence with the original product has been verified. Preliminary data from the post-authorisation PATRO study confirm the efficacy and safety of the biosimilar product in comparison with data from clinical trials. However, final results must be evaluated at the end of the study, which will provide additional information about the long-term efficacy and safety of the biosimilar drug. Resumen: Introducción: La hormona de crecimiento humana recombinante biosimilar (rhGH) fue el primer medicamento autorizado por la Agencia Europea del Medicamento (EMA), en el año 2006, por la vía de registro biosimilar. Se aprobó su uso para el tratamiento del déficit de hormona de crecimiento, trastorno de crecimiento asociado al síndrome de Turner, trastorno de crecimiento asociado a insuficiencia renal crónica, síndrome de Prader-Willi, trastorno de crecimiento en niños/adolescentes nacidos pequeños para su edad gestacional y como terapia de sustitución en adultos con deficiencia pronunciada de hormona de crecimiento. Materiales y métodos: Esta revisión se centra en las evidencias científicas publicadas en los últimos 10 años, incluyendo los ensayos clínicos utilizados para conseguir la aprobación por parte de la EMA y los estudios más relevantes que evalúan el medicamento en la práctica clínica habitual. Resultados: La equivalencia entre este biosimilar de rhGH y su producto de referencia ha sido demostrada en los ensayos clínicos publicados por Romer et al. y López-Siguero et al. Asimismo, los estudios del fármaco realizados en condiciones de práctica clínica habitual confirman su eficacia y seguridad a largo plazo, así como la ausencia de impacto clínico al cambiar el producto original por el biosimilar. Conclusión: Desde su aprobación, el número de pacientes que reciben esta medicación ha experimentado un continuo crecimiento. Los datos preliminares del estudio postautorización PATRO indican que la eficacia y seguridad del fármaco se correlaciona con la obtenida en los ensayos clínicos. No obstante, aún queda pendiente evaluar los resultados definitivos del estudio que aportarán información adicional sobre la eficacia y seguridad del fármaco a largo plazo.